Rancang Bangun Sistem Informasi Penjualan Pada PT. Supramedika Prima Cabang Surabaya - Martfriena, Adelina; Tjandrarini, A.B.; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2015)
PT. Supramedika Prima Cabang Surabaya is the sole distributor of selling health equipment and drugs reagent in eastern indonesia based in jakarta. The sales activity on PT. Supramedika Prima currenty includes approval reservation, procedures of payment (for cash or credit), delivery order, to the procedure billing if payment made on credit. As an evaluation on company requires information of sales made each month. Incomplete information owned currently can obstruct activities evaluation selling by sales manager especially ifthe transaction data being tucked or not copied. The solution to take over those problems were made a sistem which can be used to save and manage sales data, andÂ  generate information which is needed as evaluation. That solution is an sales information system. Information system which has been made was adapted by company requirement. Sales data which has been saved and proceed by a system was used to generate company requirement report. The conclusion of test result, this sales information system can generate nine (9) reports which can be used by manager as an evaluation. This information system has a billing remainder system that can be showed when sales staf did login, this system can be used as a tools which can help bill collector staf to remain bill schedule for customer.Keywords: Application, Information Systems, Sales, Health Equipment, Reagent, Evaluation